(untitled) (Research, Society and Development, 2021)
The aim of the present study was to evaluate the irradiance of different light-curing devices when subjected to the use of different types of biological protection barriers. The tested devices were: Bluephase N. Radii-Cal and VALO wireless. The biosafety barriers were: Polyethylene and Polyvinyl Chloride with one and two turns. The tips of the devices had their diameters measured on a digital pachymeter and the area of each tip was calculated. The power (mW) of the devices was measured with a potentiometer for 20 seconds and three times for each device. Then. the irradiance (mW / cm²) was calculated by the quotient of the power of the device by the cross-sectional area of the tip of the photoactivator. The irradiance data for each group were collected and subjected to two-way ANOVA analysis of variance (SPSS). with Tukey’s post-hoc. As a result. a statistically significant interaction between the different types of light-curing device and translucent protection barriers (p < 0.05) were observed. It can be concluded that the protective barrier made with 1-turn polyvinyl chloride demonstrated the best irradiance results and among the light-curing devices. regardless of the type of barrier used. Bluephase obtained the best irradiance results. followed by Valo and Radii.